INTERSECTIONS OF ARTS. STRUCTURAL AND LANGUAGE ANALOGIES - IONAȘCU, Stelian (Studia Universitatis Babes-Bolyai Musica, 2018)
Analysing and interpreting the artistic phenomena outlines a fact: arts do intersect, stimulating one another on their ascending way, mutually increasing their force of expression on behalf of the artist, and their measure of understanding on behalf of the recipient. These intersections, transpositions and equivalences between arts, both in attitude and content, could be explained whether by the insufficiency of specific means for a certain artistic field (i.e. music, painting, literature) and thus, a need to ‘borrow’ them from elsewhere, whether by the assumption that they are results of deliberate actions, owing their riches and beauty to this very act of ‘borrowing’, without ever affecting the specificity of any of the arts involved. Consequently, we might come across a parlance of colour and a colouring of speech, a musicality of poetry and poetry of music. Paradoxically, we perceive a colouring of a sculpture, determined by the different ways of light shining on the textures of a certain masterpiece, depending on its volumes and materiality.